1957
DOI: 10.1017/s0031182000021934
|View full text |Cite
|
Sign up to set email alerts
|

Development of Paramphistomum sukari Dinnik, 1954 (Trematoda: Paramphistomidae) in a snail host

Abstract: The development of Paramphistomum sukari Dinnik in a snail host is described with the emphasis laid on the succession of redial generation.The sporocyst gives birth to about twenty to thirty rediae. These rediae of the first generation commence with the production of daughter rediae then enter the second phase of their productivity during which they produce cercariae. The daughter rediae, or the rediae of the second generation, repeat these two phases during their lives, commencing with redial production and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1961
1961
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 2 publications
(2 reference statements)
1
15
0
Order By: Relevance
“…It is possible that C. microbothrium or other paramphistomes play the same role in increasing the susceptibility of some planorbid snails to other species of Schistosoma Weinland, 1858 including S. haematobium (Bilharz, 1852) Weinland, 1858 and S. mansoni Sambon, 1907, both significant human parasites. Infection of Biomphalaria pfeifferi Krauss, 1848, an important snail host of S. mansoni, with Paramphistomum sukari Dinnik, 1954was reported (Dinnik and Dinnik, 1954, 1957Dinnik, 1965;Graber and Daynes, 1974). Our finding of a paramphistome infection {P4} in Biomphalaria sudanica Martens, 1870, another important snail host of S. mansoni in Africa, is of interest in this regard.…”
Section: Discussionmentioning
confidence: 55%
“…It is possible that C. microbothrium or other paramphistomes play the same role in increasing the susceptibility of some planorbid snails to other species of Schistosoma Weinland, 1858 including S. haematobium (Bilharz, 1852) Weinland, 1858 and S. mansoni Sambon, 1907, both significant human parasites. Infection of Biomphalaria pfeifferi Krauss, 1848, an important snail host of S. mansoni, with Paramphistomum sukari Dinnik, 1954was reported (Dinnik and Dinnik, 1954, 1957Dinnik, 1965;Graber and Daynes, 1974). Our finding of a paramphistome infection {P4} in Biomphalaria sudanica Martens, 1870, another important snail host of S. mansoni in Africa, is of interest in this regard.…”
Section: Discussionmentioning
confidence: 55%
“…canforfu.~ takc three to five weeks to reach the infective stage at 50°F, and at 40'F development ceases altogether. Also Dinnik and Dinnik (1958) in Kenya found that no larvae were produced below the temperature range of a mean maximum of 70" and a mean minimum of 50°F.…”
Section: Resultsmentioning
confidence: 95%
“…Despite their ubiquitous presence, our current knowledge of the fundamental molecular and developmental biology of rumen fluke is limited, particularly in comparison to other trematodes of veterinary significance such as the liver fluke, Fasciola hepatica. For instance, histochemical staining, as well as morphological and ultrastructural studies, have detailed the anatomy of several paramphistome species [3,5,28,29], but such work has largely focused on larval stages within the intermediate host or adult rumen-dwelling flukes that are easier to collect, mostly belonging to tropical and sub-tropical species of paramphistome to date. To our knowledge, the development of various organ systems (e.g.…”
Section: Highly Prevalent But Poorly Understood: How Much Do We Know?mentioning
confidence: 99%